The Routledge atlas of Central Eurasian affairs - Brunn, Stanley D. (Routledge, 2009)
Providing concisely written entries on the most important current issues in Central Asia and Eurasia, this atlas offers relevant background information on the region's place in the contemporary political and economic world. Features include:Profiles of the constituent countries of Central Asia, namely Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and UzbekistanProfiles of Mongolia, western China, Tibet, and the three Caucasus states of Armenia, Azerbaijan, and GeorgiaTimely and significant original maps and data for each entry>